"Madura is My Home, Java Is My Language" Javanese Cultural Acculturation in Bangkalan Regency, Madura Island - Eka Nur Musfi’atin; Lina Puryanti (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Language and identity are two interrelated things. As a means of active communication, language is used in the daily life of mankind, which functions and plays an active role in the process of cultural preservation in an area. This study aims to find out how the use of Javanese in the coastal area of Madura Island is mainly in the three villages that are the main research objects, namely the villages of Tajungan, Kauman, and Junganyar in the Kamal and Socah sub-districts, Bangkalan Regency, East Java Province. This research is in the form of descriptive qualitative research using Yin's research method based on 5 stages of research with a sociolinguistic theory approach that examines the concept of bilingualism applied in an area or community in the communication process. The results of the study revealed that 9 points of findings were related and able to answer the formulation of the problem related to the geographical factors of the border area of the three research villages, as well as the process and impact of cultural acculturation which were described in detail in the discussion points and conclusions of this study.